Breast reconstruction after prophylactic contralateral mastectomy - Raidel Deucher Ribeiro; Evandro Luiz Mitri Parente (Revista Brasileira de Cirurgia Plástica)
Introduction: Prophylactic contralateral mastectomy (PCM) has been increasingly indicated in recent years for patients outside of the high-risk group, although its cancer benefit in terms of survival remains controversial. The possibility of breast reconstruction is one of the most important factors for this indication. The objective of this study was to evaluate the indications and complications after immediate breast reconstruction in patients who underwent PCM. Method: Indications and complications were evaluated in patients who underwent immediate breast reconstruction after therapeutic mastectomy and PCM. Results: Of the 13 patients in the study, only 4 had a high-risk indication for PCM (strong family history). The other indications were desire for symmetry, control of anxiety related to neoplasm recurrence, and age-related risk. Only minor complications occurred, without a need for reoperation, in 4 of the 13 patients (30.76%). Eight complications (30.76%) in 26 reconstructed breasts were recorded. Conclusion: The number of PCM procedures has been increasing and the indications transcend the oncological point of view, directly influencing the performance of plastic surgeons with respect to the planning and complications of breast reconstruction.